ChemInform Abstract: Mechanochemical Reactions and Syntheses of Oxides. Issue 43 (7th October 2013) - Sepelak, Vladimir; Duevel, Andre; Wilkening, Martin; Becker, Klaus‐Dieter; Heitjans, Paul
Abstract Review: 61 refs.